The fitness connection of antibiotic resistance - Fuzi, Miklos (Frontiers in Microbiology, 2025)
More than three decades ago multidrug-resistant (MDR) clones of the pathogens: Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Clostridioides difficile, Enterococcus faecium, Pseudomonas aeruginosa and Acinetobacter baumannii have started to disseminate across wide geographical areas. A characteristic feature of all these MDR lineages is the carriage of some mutations in the quinolone resistance-determining regions (QRDRs) of DNA gyrase and topoisomerase IV which besides conferring resistance to fluoroquinolones are associated with a fitness benefit. Several lines of evidence strongly suggest that extra fitness conferred by these mutations facilitated the dissemination of the international MDR lineages. MDR pathogens require extra energy to cover the fitness cost conferred by the excess antibiotic resistance gene cargo. However, extra energy generated by upgraded metabolic activity was demonstrated to increase the uptake of antibiotics enhancing susceptibility. Accordingly, MDR bacteria need additional positive fitness schemes which, similarly to the QRDR advantage, will not compromise resistance. Some of these, not clone-specific effects are large genomes, the carriage of low-cost plasmids, the transfer of plasmid genes to the chromosome, the application of weak promoters in integrons and various techniques for the economic control of the activity of the integrase enzyme including a highly sophisticated system in A. baumannii. These impacts – among others – will confer a fitness advantage promoting the spread of MDR pathogens. However, even the potential of extra fitness generated by the combined effect of various schemes is not without limit and virulence-related genes or less relevant antibiotic resistance gene cargoes will often be sacrificed to permit the acquisition of high-priority resistance determinants. Accordingly major MDR clone strains are usually less virulent than susceptible isolates. In summary, a fitness approach to the research of antibiotic resistance is very useful since the fitness status of MDR bacteria seem to profoundly impact the capacity to disseminate in the healthcare setting.